Comparison of the Prevention of Esophageal Stricture Between Oral Prednisolone Alone and Oral Prednisolone Combined with Nasogastric Tube in Superficial Esophageal Cancer After Endoscopic Submucosal Dissection - Lihong Teng; Xiaoyun Yang; Jin Ding (Turkish Journal of Gastroenterology, 2024)
Background/Aims: There is a lack of effective and safe methods for preventing esophageal stricture after large endoscopic submucosal dissection (ESD) in patients with superficial esophageal cancer. We aimed to compare the effectiveness of oral prednisolone alone versus a combination of oral prednisolone and nasogastric tube in preventing esophageal stricture following extensive ESD. Materials and Methods: We retrospectively gathered clinical data from a single center on patients with early esophageal cancer who underwent ESD. Patients were categorized into 2 groups: the steroid group (receiving only oral prednisolone) and the steroid+nasogastric tube retention (NGT) group. We analyzed the incidence of esophageal stricture and identified risk factors for its development. Results: The study included 79 patients, with 30 in the steroid group and 49 in the steroid+NGT group. The incidence of stricture was significantly higher in the steroid group (9/30, 30.0%) compared to the steroid+NGT group (3/49, 6.1%) (P = .004). Notably, we observed a significant difference in the stricture rates between the 2 groups, particularly in patients with a complete circumferential defect (100% and 16.7%) (P = .015). Multivariate logistic regression analysis revealed that a full circumferential defect of the esophageal mucosa (OR 12.501; 95% CI 1.907, 81.047; P = .008), invasion depth beyond the lamina propria (OR 5.635; 95% CI 1.039, 30.559; P = .045), and the absence of NGT retention (OR 12.896; 95% CI 2.099, 79.219; P = .006) were independent risk factors predicting the development of a stricture. Conclusion: The combination of steroids with NGT retention is more effective than using oral steroids alone in preventing esophageal stricture after extensive ESD. Cite this article as: Teng L, Yang X, Hong Y, Ding J. Comparison of the prevention of esophageal stricture between oral prednisolone alone and oral prednisolone combined with nasogastric tube in superficial esophageal cancer after endoscopic submucosal dissection. Turk J Gastroenterol. 2024;35(6):481-487.